Off-Balance Sheet Analysis Toward Risk-Adjusted Performance - Ignatia Ryana Widyatini; Raymundo Patria Hayu Sasmita (The Indonesian Journal of Accounting Research, 2021)
Abstract: Off balance sheet is an activity undertaken by a financial institution, but not seen or recorded on the balance sheet because such activities do not cause or involve ownership of assets and the issuance of debt instruments (Saunders & Cornett 2003). Off Balance Sheet activities can be obtained through income derived from non-interest income. The off balance activity is initiated by the banking industry with the aim of creating diversification in obtaining optimal bank's returns. This study aims to investigate the effect of revenue diversification from off balance sheet activity toward Bank’s risk-adjusted performance. This research was conducted in several Commercial Banks in Indonesia. The data collection was based on purposive sampling and statistically analysed using Eviews version 9.2. The results of this research showed that revenue diversification from off balance sheet activity bears positive effects toward Commercial Bank’s risk-adjusted performance in Indonesia. Off balance sheet activity was measured by non-interest income reported in the income statement.. Keywords: off-balance-sheet, diversification, risk-adjusted, non-interestAbstrak— Off balance sheet adalah aktivitas yang dilakukan oleh institusi keuangan namun tidak nampak pada neraca karena aktivitas ini tidak menyebabkan dan melibatkan kepemilikan asset serta tidak menimbulkan penerbitan hutang (Saunders & Cornett 2003). Pendapatan dari aktivitas Off Balance Sheet dapat diperoleh melalui pendapatan yang berasal dari pendapatan-non bunga. Aktivitas off balance sheet dimulai oleh industri perbankan dengan tujuan menciptakan diversifikasi dalam memperoleh pengembalian bank yang optimal. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh diversifikasi pendapatan yang timbul dari aktivitas off balance sheet terhadap tingkat pengembalian berbasis risiko pada industri perbankan. Penelitian ini dilakukan di beberapa bank umum di Indonesia. Pengumpulan data berdasarkan purposive sampling dan dianalisis secara statistik menggunakan Eviews versi 9.2. Hasil penelitian menunjukkan bahwa diversifikasi pendapatan dari aktivitas off-balance sheet berpengaruh positif terhadap kinerja yang disesuaikan dengan risiko pada perbankan di Indonesia. Aktivitas off Balance sheet diukur melalui aktivitas yang menimbulkan pendapatan non-bunga yang dilaporkan pada laporan laba rugi. Kata Kunci: off-balance-sheet, diversifikasi, risiko, non-bunga